Electronic application for rabies management improves surveillance, data quality, and investigator experience in Haiti - Schrodt, Caroline A.; Dilius, Pierre; Gibson, Andrew D.; Crowdis, Kelly; Fénelon, Natael; Ross, Yasmeen; Bonaparte, Sarah; Gamble, Luke; Lohr, Frederic; Joseph, Haïm C.; Wallace, Ryan M. (Frontiers in Veterinary Science, 2023)
Background: Integrated bite case management (IBCM) is a multi-sectoral response to animal-bites which reduces human and canine rabies mortality through animal quarantine, bite-victim counseling, and vaccination tracking. Haiti’s national rabies surveillance program was established in 2013 using paper-based IBCM (pIBCM) with adoption of an electronic smartphone application (eIBCM) in 2018. Methods: We evaluated the feasibility of implementing the electronic app in Haiti and compared pIBCM and eIBCM data quality collected January 2013 – August 2019. Deaths prevented, cost-per-death averted, and cost-per-investigation during use of pIBCM and eIBCM were estimated using a previously validated rabies cost-effectiveness tool that accounted for bite-victim demographics; probability of acquiring rabies; post-exposure prophylaxis; and costs including training, supplies, and salaries. We compared pIBCM and eIBCM based on data comprehensiveness, completeness, and reporting efficiency. Surveys were administered to IBCM staff to evaluate the usefulness, simplicity, flexibility, and acceptability of eIBCM. Results: Of 15,526 investigations, 79% were paper-based and 21% electronic. IBCM prevented 241 (estimated) human rabies deaths. Using pIBCM, cost-per-death averted was $2,692 and the cost-per-investigation was $21.02; up to 55 data variables were collected per investigation; data transmission took 26 days to reach national staff, and 180 days until analysis. Using eIBCM, the cost-per-death averted was $1,247 and the cost-per-investigation was $22.70; up to 174 data variables were collected per investigation; data transmission took 3 days to reach national staff, and 30 days until analysis. Among 12,194 pIBCM investigations, 55% were mappable by commune, compared to 100% of eIBCM investigations mappable by GPS. Animal case definitions were incorrectly ascribed by investigators in 5.5% of pIBCM investigations and zero for eIBCM; typically, errors were in determining probable vs suspect case assignments. Overall, eIBCM was well-accepted by staff, who reported the app is easy-to-use, facilitates investigations, and compared to pIBCM hastens data reporting. Discussion: In Haiti, eIBCM showed improved data completeness, data quality, and shorter notification times with minimal increase in operational cost. The electronic app is simple-to-use and facilitates IBCM investigations. Rabies endemic countries could refer to eIBCM in Haiti as a cost-effective means to reduce human rabies mortality and improve surveillance capacity.